Glycosphingolipids on Human Myeloid Cells Stabilize E-Selectin–Dependent Rolling in the Multistep Leukocyte Adhesion Cascade. Issue 4 (April 2016) - Mondal, Nandini; Stolfa, Gino; Antonopoulos, Aristotelis; Zhu, Yuqi; Wang, Shuen-Shiuan; Buffone, Alexander; Atilla-Gokcumen, G. Ekin; Haslam, Stuart M.; Dell, Anne; Neelamegham, Sriram
Abstract : Objective—: Recent studies suggest that the E-selectin ligands expressed on human leukocytes may differ from those in other species, particularly mice. To elaborate on this, we evaluated the impact of glycosphingolipids expressed on human myeloid cells in regulating E-selectin-mediated cell adhesion. Approach and Results—: A series of modified human cell lines and primary neutrophils were created by targeting UDP-Glucose Ceramide Glucosyltransferase using either lentivirus-delivered shRNA or CRISPR-Cas9-based genome editing. Enzymology and mass spectrometry confirm that the modified cells had reduced or abolished glucosylceramide biosynthesis. Glycomics profiling showed that UDP-Glucose Ceramide Glucosyltransferase disruption also increased prevalence of bisecting N-glycans and reduced overall sialoglycan expression on leukocyte N- and O-glycans. Microfluidics-based flow chamber studies demonstrated that both the UDP-Glucose Ceramide Glucosyltransferase knockouts and knockdowns display ≈60% reduction in leukocyte rolling and firm adhesion on E-selectin bearing stimulated endothelial cells, without altering cell adhesion to P-selectin. Consistent with the concept that the glycosphingolipids support slow rolling and the transition to firm arrest, inhibiting UDP-Glucose Ceramide Glucosyltransferase activity resulted in frequent leukocyte detachment events, skipping motion, and reduced diapedesis across the endothelium. Cells bearing truncated O- and N-glycans also sustained cell rolling on E-selectin, although their ability to be recruited from free fluid flow was diminished. Conclusions—: Glycosphingolipids likely contribute to human myeloid cell adhesion to E-selectin under fluid shear, particularly the transition of rolling cells to firm arrest. Abstract : Supplemental Digital Content is available in the text.